The Impact of ICT on Labour Productivity – Europe vs. U.S. - Trpeski, Predrag; Trenovski, Borce; Merdzan, Gunter; Kozheski, Kristijan (EDP Sciences, 2021)
Research background: The European economy has been experiencing declining productivity growth rates since the 1970s despite high investments in information and communication technologies (ICT). Investments in ICT are considered a key driver of productivity growth that serves as a basis for further improvements in living standards. However, despite the emergence of new technologies and industries, especially after 1995, European productivity growth has slowed and lagged behind the United States. The critical question is why? Purpose of the article: This article aims to examine the effects of ICT on the European labour market in the period when machines and systems such as artificial intelligence, new information technologies, the Internet of things, and other technologies are becoming increasingly interconnected and intertwined. Additionally, the article examines the key reasons why European productivity lags behind the U.S. and explains them. Methods: The panel regression method analyzes the productivity lag of selected European developed countries and emerging markets in 2007-2019. The article additionally makes a qualitative analysis of the benefits of new technologies on productivity in Europe compared to the U.S. Findings & Value added: The results of the econometric analysis applied in this article confirm the positive but insignificant impact of ICT investments on the labour productivity of the case of European developed countries in the post-Great Recession period. Thus, the article fills the gap in the research literature regarding the relationship between ICT investments and the labour productivity of selected European countries.
Keywords: ICT; labour productivity; multifactor productivity; Europe, the U.S